Containment beyond detention: The hotspot system and disrupted migration movements across Europe. (December 2020) - Tazzioli, Martina; Garelli, Glenda
This article deals with the ways in which migrants are controlled, contained and selected after landing in Italy and in Greece, drawing attention to strategies of containment aimed at disciplining mobility and showing how they are not narrowed to detention infrastructures. The article starts by tracing a genealogy of the use of the term 'hotspot' in policy documents and suggests that the multiplication of hotspots-like spaces is related to a reconceptualisation of the border as a critical site that requires prompt enforcement intervention. The article moves on by investigating the mechanisms of partitioning, identification and preventive illegalisation that are at stake in the hotspots of Lampedusa and Lesbos. Hotspots are not analysed here as sites of detention per se: rather, the essay turns the attention to the channels of forced mobility that are connected to the Hotspot System, focusing in particular on the forced transfers of migrants from the Italian cities of Ventimiglia and Como to the hotspot of Taranto. The article concludes by analysing channels of forced mobility in the light of the fight against 'secondary movements' that is at the core of the current European Union's political agenda, suggesting that further academic research could engage in a genealogy of practices of migration containment.